1999
DOI: 10.1021/jp983887i
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Metal Ion Production in Sputtering dc Glow Discharge Plasmas:  Characterization by Electronic State Chromatography

Abstract: The sputtering dc glow discharge is a stable and intense source of a wide variety of metal ions for use in ion/molecule studies. We have examined factors influencing the formation of metastable excited states of sputtered species in this device using the electronic state chromatography (ESC) technique. These determinations are essential if the glow discharge is to be used as a source of metal ions for subsequent reaction, since the electronic configuration of the metal can dramatically affect its reactivity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
71
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 26 publications
11
71
0
Order By: Relevance
“…Initial attempts using a number of experimental conditions resulted in the observation of only one peak in our drift studies. This is consistent with the results of Taylor et al who used a glow discharge metal ion source [6]. More recent studies have produced the results shown in Figure 5.…”
Section: Identification Of States: Dependence On Electron Energysupporting
confidence: 91%
See 4 more Smart Citations
“…Initial attempts using a number of experimental conditions resulted in the observation of only one peak in our drift studies. This is consistent with the results of Taylor et al who used a glow discharge metal ion source [6]. More recent studies have produced the results shown in Figure 5.…”
Section: Identification Of States: Dependence On Electron Energysupporting
confidence: 91%
“…Some of the tailing may be a result of the pulsing where ions at the end of the pulse will be accelerated by the return of the pulsing lens to the more positive trapping potential. Such asymmetry has been observed previously for all third-row transitionmetal ions (including W ϩ ) studied by Taylor et al [6]. They discuss the phenomenon extensively and note that the tails correlate with the observation of other species (metal oxides or metal hydrates), which have lower mobilities.…”
Section: Experimental Conditions For Separation: Pulse Conditionssupporting
confidence: 73%
See 3 more Smart Citations